Determination of spectrum shaping factor in nuclear reactor AHWR-CF by Monte Carlo method for material characterization using neutrons. (2021) - Bhandari, Deep; Kishore Mallick, Amod; Samanta, Sudipta; Sarkar, Anindita; Kumar, Rajeev; Kannan, Umasankari
Abstract: Activation analysis is a well-known radio-analytical technique to carry out the material characterization using neutrons. In this, the sample of material is irradiated in an ambient neutron flux and the induced radioactivity is studied to infer the composition of material. K0 based neutron activation analysis (k0 -NAA) is a method used for characterising variety of materials using neutrons. Knowledge of neutron energy spectrum and it's shaping factor (α) at neutron irradiation location is essential for application of (k0 -NAA) method. The objective of the present work is to determine α at central location in AHWR-Critical Facility, a nuclear reactor at Bhabha Atomic Research Center, Mumbai, India. The determination of α was carried out by various analytical methods. The basic inputs required for determination of α were produced by modelling the reactor using in-house developed Monte Carlo code PATMOC. The results were cross checked by generating neutron energy spectrum in the reactor.